MANAGING AN ORGANIZATION'S ONLINE REPUTATION IN THE DIGITAL ECONOMY (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article examines the specifics of online reputation management in the digital economy, where digital communications, social media, search engines, and user review platforms significantly influence public opinion and the competitiveness of companies. It analyzes the key factors that determine an organization's reputational capital in the digital environment, including the quality of digital communications, the speed of response to feedback, user-generated content management, and the use of information monitoring tools. Particular attention is paid to modern technologies for data analysis, artificial intelligence, and the automation of reputation management processes, which enable the timely identification of potential reputational risks, forecasting changes in public sentiment, and making effective management decisions. Practical approaches to fostering a positive digital image for an organization, minimizing the impact of information crises, and increasing trust among consumers and partners are considered. It is concluded that the integrated use of digital monitoring tools, analytics, and strategic communications management helps strengthen an organization's reputation, increase its resilience to information threats, and ensure long-term competitive advantages in the context of the digital transformation of the economy.